Functional and Immune Modulatory Characteristics of Bone Marrow Mesenchymal Stromal Cells in Patients With Aplastic Anemia: A Systematic Review - Atmar, Khaled; Tulling, Adam J.; Lankester, Arjan C.; Bartels, Marije; Smiers, Frans J.; van der Burg, Mirjam; Mohseny, Alexander B. (Frontiers in Immunology, 2022)
Background: In most patients with aplastic anemia (AA), the diagnosis is limited to a description of the symptoms. Lack of understanding of the underlying pathophysiological mechanisms causing bone marrow failure (BMF), hampers tailored treatment. In these patients, auto-immune cell-mediated destruction of the bone marrow is often presumed to be the causative mechanism. The status of the bone marrow microenvironment, particularly the mesenchymal stromal cell (MSC) component, was recently suggested as a potential player in the pathophysiology of AA. Therefore, functional, and immune modulatory characteristics of bone marrow MSCs might represent important parameters for AA. Objective: To conduct a systematic review to evaluate in vitro functional properties of MSCs derived from patients with AA compared to healthy controls. Methods: According to PRISMA guidelines, a comprehensive search strategy was performed by using online databases (Pubmed, ISI Web of Science, Embase, and the Cochrane Library). Studies reporting on phenotypical characterization, proliferation potential, differentiation capacity, immunomodulatory potential, and ability to support hematopoiesis were identified and screened using the Rayyan software tool. Results: 23 articles were included in this systematic review, describing a total of 324 patients with AA and 285 controls. None of the studies identified a significant difference in expression of any MSC surface marker between both groups. However, AA-MSCs showed a decreased proliferation potential, an increased tendency to differentiate into the adipogenic lineage and decreased propensity towards osteogenic differentiation. Importantly, AA-MSCs show reduced capacity of immunosuppression and hematopoietic support in comparison to healthy controls. Conclusion: We conclude that there are indications for a contribution of MSCs in the pathophysiology of AA. However, the current evidence is of poor quality and requires better defined study populations in addition to a more robust methodology to study MSC biology at a cellular and molecular level. Future studies on bone marrow microenvironment should aim at elucidating the interaction between MSCs, hematopoietic stem cells (HSCs) and immune cells to identify impairments associated with/causing BMF in patients with AA.